Pengaruh Suhu dan Variasi Ukuran Terhadap Mutu Keripik Jeruk BW (Citrus reticulata Blanco) dengan Menggunakan Penggorengan Vakum (Vacuum Frying) - Asmara, Sandi; Suharyatun, Siti; Warji, Warji; Triningsih, Widi (Jurnal Agricultural Biosystem Engineering, 2025)
The BW orange is one of the horticultural commodities that is susceptible to quality deterioration but has the potential to be processed into chips using vacuum frying. There are important factors in this study, namely frying temperature and the size variation of the fruit used. The objective of this research is to determine the effect of frying temperature and fruit size variation on the physical characteristics (yield, moisture content, texture, and color) of BW orange chips produced through vacuum frying. The method used in this research is a Two-Factorial Randomized Block Design (RAL), with the first factor being frying temperature (60°C, 70°C, and 80°C) and the second factor being fruit size variation, which includes one segment, two segments, and three segments of BW orange. The sample testing was based on the parameters of yield, moisture content, texture, color, and organoleptic tests. Based on the results of the research, it was found that frying temperature significantly affected the yield, moisture content, color, crispness, and frying time of the chips. However, it did not have a significant effect on the aroma and taste of the chips. The fruit size variation significantly affected the yield and frying time of the chips, but it did not have a significant effect on moisture content, aroma, taste, color, and crispness. Based on the organoleptic test, panelists preferred the BW orange chips with the treatment T3P1 (frying temperature of 80°C and one segment fruit size), with a total acceptance score of 3.25 (slightly liked). Keywords: BW Oranges, Chips, Size Variation, Temperature, Vacuum Frying